Validation of the Italian version of the UNESP–Botucatu unidimensional composite pain scale for the assessment of postoperative pain in cattle - della Rocca, Giorgia; Brondani, Juliana Tabarelli [UNESP]; de Oliveira, Flávia Augusta; Crociati, Martina; Sylla, Lakamy; Elad Ngonput, Agnes; Di Salvo, Alessandra; Luna, Stelio Pacca Loureiro [UNESP] (Elsevier, 2017)
Objective The aim of this study was to validate the Italian version of the UNESP–Botucatu Unidimensional Composite Pain Scale (UCPS-IV) for assessing postoperative pain in cattle. Study design Video analysis and psychometric testing. Animals A total of 40 Nellore cattle, age 2–3 years, weighing 365 ± 51 kg. Methods An English version of the scale was translated to Italian and back translated to English to ensure semantic equivalence. A total of four Italian observers and the researcher who developed the original scale (considered as the gold standard) analysed videos of 40 cattle previously subjected to orchiectomy (recorded for each cattle at four predetermined timepoints during the perioperative period) unaware of the videos’ timepoint. They assigned a pain score [ranging from no pain (0) to severe pain (10)] using the Italian version of the scale and verified the need for analgesic treatment for each animal. The obtained scores were subjected to psychometric validity, responsiveness and reliability tests. Results The factor analysis of the scale resulted in a one-factor solution. Significant changes in pain scores in response to surgery and analgesics confirmed not only the content and construct validity, but also responsiveness. The agreement between the researcher who developed the original scale and the blinded observers and the correlation between the pain scores determined by the scale and those determined by three classical unidimensional pain scales confirmed criterion and concurrent validity. Internal consistency of the scale was excellent. Inter- and intrarater reliability ranged from moderate to good and from moderate to very good for all scale items, respectively, supporting reproducibility and stability. The cut-off point for rescue analgesia calculated by the receiver operating characteristic curve was > 3. Conclusions and clinical relevance The results confirm that the UNESP–Botucatu UCPS-IV appears to be a valid and reliable tool for the assessment of postorchiectomy pain in the bovine species. The determination of a cut-off point for rescue analgesia is also helpful for guiding analgesic therapy.
Keywords: bovine; castration; pain scoring systems; psychometric testing